King Sejong the Great ì„¸ì¢…ëŒ€ì™• (1397-1450): His Contribution in the Field of the Hangeul Alphabet and Law - Iswanto, Sufandi; Kusnafizal, Teuku; Haikal, Muhammad; Azis, Abdul; Kesuma, T. Bahagia (Bina Nusantara University, 2022)
The research aimed to describe the life history of King Sejong the Great and his contribution to the field of alphabet and law, especially law for convict, marriage, and heir. The method applied in the research was the historical method. The results show that Korea is in a golden age because of his policies during his leadership. His most outstanding contribution is the hangeul alphabet which gradually replaced idu and hanja. In addition, in the field of law or policy regarding prisoner sentences, the law must be fair and adjusted to the age limit, and the community must understand the law. Marriage law where women can only marry when they are 14 years old. The last is the law of heirs, which divides fairly and is no longer patriarchal. These policies are related to moral ethics, virtue, truth, and wisdom based on Confucianism.